The Effect of Business Mentoring on Students’ Competence in Teaching Factory Management: Pengaruh Mentoring Bisnis terhadap Kompetensi Siswa pada Pengelolaan Teaching Factory - Rikhaul, Aulia (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2025)
Data from Indonesia’s Central Bureau of Statistics (BPS) in 2024 indicate that the open unemployment rate among Vocational High School (SMK) graduates remains the highest (9.01%), suggesting a persistent gap between graduate competencies and labor-market needs. Teaching Factory programs are designed to bridge schools and industry, yet early observations show that implementation is often constrained by limited authentic practice and minimal industry involvement. This study examines the statistical relationship between business mentoring and students’ competence in managing Teaching Factory activities at Stigma Resto, SMKN 3 Sukoharjo. A quantitative cross-sectional survey was conducted with 67 eleventh-grade students participating in the Teaching Factory program. Data were collected through online questionnaires, validated using Aiken’s V and Pearson item-total correlations, and analyzed using simple linear regression. The results demonstrate that business mentoring is positively and significantly associated with student competence (p = 0.000 < 0.05; β = 0.650; r = 0.709), explaining 50.2% of the variance in competence (R² = 0.502). These findings highlight business mentoring as a key strategy to strengthen students’ technical and managerial capabilities while reinforcing Teaching Factory implementation through sustained school–industry collaboration. Future studies should expand the model by incorporating additional internal and external factors affecting Teaching Factory performance.